Study on leave image processing with application in herbal classification and early detection of chili plant disease - Zulkifli Husin (School of Computer and Communications Engineering, 2016)
The scope of this research is focused on approaches to herb species classification and early detection of plant chili disease using digital images processing and neural network algorithm. The aim is to review the current techniques and applications, to motivate greater efforts to solve a range of important techniques, and practical problems in both applications. The scope also covers thorough implementation of herb species classification and early detection of plant chili disease.